Renal failure parathyroidectomy – Is pre-operative imaging worthwhile?. Issue 4 (August 2019) - Spence, Robert A.J.; Patterson, Timothy J.; Currie, Peter; Convie, Liam; Tong, Lioe; Brown, Tim; Spence, Roy A.J.
Abstract: Background: Tertiary hyperparathyroidism is a significant issue in renal failure patients and some require surgery to control their serum calcium. A number of imaging techniques are used to localise the position of the parathyroid glands prior to surgery. Currently, a combination of ultrasound and isotope preoperative localisation imaging is accepted as useful in parathyroid surgery for primary disease. However, the use of pre-operative imaging in parathyroid surgery in renal failure patients is uncertain. The role of pre-operative imaging of the parathyroid glands in patients with renal failure hyperparathyroidism was assessed with imaging outcomes compared to operative and pathological findings in two cohorts of patients undergoing parathyroid surgery – primary and tertiary. Methods: All data were collected prospectively over a 10-year period (2003–2013) from the practice of a single surgeon. Patients were grouped into either primary hyperparathyroidism (49 patients) or tertiary hyperparathyroidism (41 patients). The majority, 63 of 90 (70%) patients, underwent both ultrasound (US) and isotope (MIBI) pre-operative imaging. Pre-operative imaging was correlated with operative and pathological findings. Findings: Comparison of the results of the two groups using ordinal regression analysis confirmed these imaging techniques are significantly more accurate in primary than tertiary parathyroid surgery ( p = 0.022). Conclusions: While accepted practice of pre-operative combined USS and MIBI imaging is essential in unilateral imaged-focused neck exploration for primary disease, these imaging techniques have a more limited use pre-operatively in renal failure parathyroidectomy.